Government for a new age : the transformation agenda - Abouchakra, Rabih; Khoury, Michel (Infinite Ideas Limited, 2015)
What is the role of government in the modern world? Global upheavals and geopolitical shifts, climate change, rapidly evolving technologies and socio-economic demographics, resource constraints, an increasingly diverse constituency and citizens more demanding expectations -- these are just some of the forces driving societal changes and transforming the context in which governments operate. Around the world governments are responding to these challenges by shifting the way they engage with citizens, and the private and third sector. This book brings together the latest thinking on modern government. It sheds light on the current trends in governance practices, operating models, processes and tools that leading governments are embracing. It explores the ways in which governments are changing their value proposition to tackle these pressing concerns and provide some answers to these questions. --